Bankometer Models for Predicting Financial Distress in Banking Industry - Laely Aghe Africa (Jurnal Keuangan dan Perbankan, 2018)
Banking is a collection of several functions of the bank, which is bank is a financial institution that focuses on profit and also social, but from the other side of the bank can also collapse and there are indications of bankruptcy, and one way to predict is to use one of the models to determine financial distress. The latest prediction model is the Bankometer Model. The objective of this research is to analyze The Bankometer Model can use to determine financial distress. A sample of this research is 111 listed bank data Indonesia Stock Exchange from 2012 to 2016, 60 for Foreign Exchange Bank and 51 for Non-Foreign Exchange Bank. Logistic Regression to analyze the data in SPSS 23 Version. The result of this study is The Bankometer Model can use to determine financial distress for Foreign Exchange Bank and Non-Foreign Exchange Bank. This research implication is for management of the company in decide regulator in a company that related to financial distress.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v22i2.2050